Antibodies to Phosphatidylethanolamine as the only Antiphospholipid Antibodies Found in Patients with Unexplained Thromboses - Sanmarco, Marielle; Alessi, Marie-Christine; Harle, Jean Robert; Sapin, Christophe; Aillaud, Marie-Françoise; Gentile, Stéphanie; Juhan-Vague, Irène; Weiller, Pierre-Jean (Thrombosis and Haemostasis, 2001)
The objective of this study was to assess the interest of antiphosphatidylethanolamine antibodies (aPE) in unexplained thrombosis (UT) defined as thrombotic episode without any of the main autoimmune and hereditary thrombophilic defects. Results from 98 UT were compared to those of (I) 142 patients with thrombophilia: 67 antiphospholipid syndrome (APS) and 75 hereditary hemostatic defects (HHD); (II) 110 patients without thrombosis: 60 with systemic lupus erythematosus (SLE) and 50 with infectious diseases (ID). As compared to controls (100 blood donors), aPE prevalence was significantly higher in both autoimmune contexts (APS: 43%; SLE: 40%, p <0.0001) and among non-autoimmune pathologies, only in UT (18%, p = 0.001) conversely to HHD (8%) or ID (10%). aPE prevalence in UT was not statistically different from that found in Primary APS (32%, p = 0.076) but lower than in Secondary APS (65%, p <0.005). In UT, aPE were mainly of IgM isotype like in Primary APS and they were found alone whereas in SLE they were always associated with classical anti-phospholipid antibodies. No significant association was found between any isotype of aPE and a site of thrombosis in UT as well as in APS. In conclusion, this study demonstrates an increase of the prevalence of aPE in patients with unexplained thrombosis. Thus, aPE investigation appears to be of interest in UT and their persistent presence could define a biological variant of APS.
Keywords: Thrombosis; antiphospholipid syndrome; antiphospholipid antibodies; antiphosphatidylethanolamine antibodies